Pembelajaran Efektif dalam Pengajaran Bahasa Arab Tingkat Menengah - Basri Mahmud; Hamzah Hamzah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Not a few Arabic teachers complain about their role as teachers and the ineffectiveness of their learning that has been done in the classroom. Many of the things that can cause this, among them because of their ignorance of the concept of effective and efficient learning, how to streamline a learning and also manage a learning, so that learning is carried out is only the transfer of knowledge (knowledge transfer) without full consideration of the goals set. In addition, teachers also lack variety of learning methods and strategies. This paper aims to uncover conceptually about effective and efficient learning in teaching Arabic at the secondary level; how indicators, principles and urgency in a learning so that teachers especially Arabic teachers know how to make an effective learning course with the realization of the goals set.